A DIFFERENT MODEL FOR ACADEMIC MENTORING: HOW RACE, MULTIPLICITY AND HOLISM INTERSECT WITH ONLINE SOCIAL MEDIA - Steele, Catherine Knight; Korn, Jenny (AoIR Selected Papers of Internet Research, 2014)
Women of color in academia are turning to the Internet to discover shared experiences of marginalization, racism, and sexism that lead to practical advice, personal edification, and especially, professional triumph. Connections among women scholars of color through online social media sites involve collapses in traditional boundaries among the personal and professional, the acceptable and taboo, and the private and public. The convergence of separate components of identity into a holistic self that is communicated online has generated a different model for the academic mentoring of women of color. We posit that online social network sites confer mentoring for women of color in academia in significant, understudied, and overlooked ways. For a study involving women of color online, Facebook is an ideal social network. African American and Latinos are more likely to use social networking sites than whites (Pew Research Center, 2012). Women are more likely than men to use Facebook and spend greater time there (Duggan & Brenner, 2013). Incorporating Facebook into our study of virtual lives often on the margins of academia provides insight into how computer-mediated social communication has transformed mentorship.